Sentiment Bias in National Basketball Association Betting. (May 2018) - Feddersen, Arne; Humphreys, Brad R.; Soebbing, Brian P.
We develop evidence of bettors with sentiment bias in the betting market on National Basketball Association (NBA) games. We use measures of team popularity (arena capacity utilization and team all-star votes received) as proxies for the presence of biased bettors. Analysis of point spreads and bet outcomes for more than 32, 000 NBA games played in 1981-2012 shows that bookmakers increase prices on games involving popular home teams, an outcome consistent with sentiment bias. These changes in prices do not translate into higher returns for bettors, suggesting that bookmakers shade point spreads to increase profits.